Iatrogenic migration of iliac stent graft that was implanted for the reason of iliac artery perforation at the beginning of TAVI into the ascending aorta during the procedure - Hudák Marek; Koščo Martin; Rašiová Maria (Sciendo, 2024)
Vascular complications are one of the substantial complications of transcatheter aortic valve implantation (TAVI). Stent graft implantation is a powerful tool for managing them.